Mucoadhesive-to-Mucopenetrating Nanoparticles for Mucosal Drug Delivery: A Mini Review - Zheng B; Liu D; Qin X; Zhang D; Zhang P (International Journal of Nanomedicine)
Bin Zheng,1,2,* Dingyi Liu,1,* Xiaowen Qin,3,* Dahong Zhang,1 Pu Zhang1 1Urology & Nephrology Center, Department of Urology, Zhejiang Provincial People’s Hospital (Affiliated People’s Hospital), Hangzhou Medical College, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Urology, The First Affiliated Hospital of Jinan University, Guangzhou, Guangdong, 510630, People’s Republic of China; 3Department of Nutrition and Food Hygiene, The National Key Discipline, School of Public Health, Harbin Medical University, Harbin, 15008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dahong Zhang, Email zppurology@163.com; Pu Zhang, Email zhangpuxjtuer@163.comAbstract: Mucosal tissue acts as a barrier between the human body’s internal environment and the external world. The mucosal tissue is shielded from injurious environmental chemicals, toxins, and pathogens by a mucus layer lining above the mucosal tissue, and meanwhile the periodic mucosal clearance accelerates the removal of mucoadhesive components. And therefore, transmucosal drug delivery is limited. Nanocarriers for mucosal drug delivery is recently developed to enhance either long retention of drugs within the mucus layer or rapid translocation of drugs across the mucus layer. Among all these types of drug delivery systems, mucoadhesive-to-mucopenetrating nanocarriers transport drugs most efficiently into targeted mucosal tissues. In this review, recent progress on the mucoadhesive-to-mucopenetrating drug delivery systems and their application are updated.Keywords: nanoparticles, mucoadhesion, mucopenetration, drug delivery